Política nacional de alfabetização e a educação da infância como biopolítica: o que dizem professoras alfabetizadoras de escolas públicas - SOUSA, Ysabelle Cardoso de (2025)
The text presents a Government Curricular Educational Policy, specifically centered on the National Evidence-Based Literacy Policy aimed at children's literacy, implemented in the form of a Decree in the Bolsonaro government in 2019. This Policy is for us understood as a device for the biopolitics of childhood. The intention of the study, in light of the Foucauldian theoretical perspective, in addition to analyzing this policy as a management strategy for child life, seeks to highlight, based on interviews with teachers who work in Early Childhood Education, where an analysis will be carried out in around your speeches. Thus, aspects of resistance and contestation surrounding the implementation of such a policy in public Early Childhood Education schools in the municipality of Abaetetuba.